Analisis Kesalahan Siswa dalam Menyelesaikan Soal Matematika Materi Persamaan dan Pertidaksamaan Linier Satu Variabel - Silvana Kurniawati; Hulaili, Sinta; Baiq Zurtania; Winda Hafifa (Griya Journal of Mathematics Education and Application, 2025)
This study aims to analyze students' errors in solving mathematical problems on the topic of linear equations and inequalities in one variable for eighth-grade students at SMPN 17 Mataram. The research approach used is qualitative descriptive, with the research subjects consisting of 15 students. Data was collected through written tests to identify the types of errors that frequently occur and the factors that cause them. The analysis results show that there are three main types of errors: (1) conceptual errors, (2) procedural errors, and (3) calculation errors. This study recommends using the discovery learning approach to improve students' understanding of the basic concepts of equations and inequalities. In addition, repeated practice and remedial learning should be provided to address procedural and calculation errors. These findings are expected to provide input for teachers in designing more effective teaching strategies. Based on the error analysis conducted, the percentage of errors made by students is as follows: conceptual errors 34% with a "Low" error rate; (2) procedural errors 45% with a "Moderate" error rate; (3) calculation errors 21% with a "Low" error rate. It can be concluded that students' understanding of calculations in the topic of linear equations and inequalities in one variable is still considered low. Teachers need to pay attention to interactive learning media strategies and provide gradual problem-solving exercises to improve students' understanding.